Drastically enhanced cation incorporation in the epitaxy of oxides due to formation and evaporation of suboxides from elemental sources - Georg Hoffmann (AIP Publishing LLC, 2021)
In the molecular beam epitaxy of oxide films, the cation (Sn, Ga) or dopant (Sn) incorporation does not follow the vapor pressure of the elemental metal sources but is enhanced by several orders of magnitude for low source temperatures. Using line-of-sight quadrupole mass spectrometry, we identify the dominant contribution to the total flux emanating from Sn and Ga sources at these temperatures to be due to the unintentional formation and evaporation of the respective suboxides SnO and Ga2O. We quantitatively describe this phenomenon by using a rate-equation model that takes into account the O2 background pressure, the resulting formation of the suboxides via oxidation of the metal source, and their subsequent thermally activated evaporation. As a result, the total flux composed of the metal and the suboxide fluxes exhibits an S-shaped temperature dependence instead of the expected linear one in an Arrhenius plot, which is in excellent agreement with the available experimental data. Our model reveals that the thermally activated regimes at low and high temperatures are almost exclusively due to suboxide and metal evaporation, respectively, joined by an intermediate plateau-like regime in which the flux is limited by the available amount of O2. An important suboxide contribution is expected for all elemental sources whose suboxide exhibits a higher vapor pressure than that of the element, such as B, Ga, In, La, Si, Ge, Sn, Sb, Mo, Nb, Ru, Ta, V, and W. This contribution can play a decisive role in the molecular beam epitaxy of oxides, including multicomponent or complex oxides, from elemental sources. Finally, our model predicts suboxide-dominated growth in low-pressure chemical vapor deposition of Ga2O3 and In2O3.